PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN TAMU DI ALAHAN PANJANG RESORT KABUPATEN SOLOK - Amel, Jullei; Waryono, Waryono; Ferdian, Feri (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research aims to know the influence of service quality toward guest satisfaction at Alahan Panjang Resort Kabupaten Solok. This research of two variables i.e service quaity and guest satisfaction. Type of this research is quantitative descriptive with causal assosiatif method. The number of samples in this research amounted to 56 people. The technique of sampling with purposive sample. Analysis technique with a simple regression test. Based on the research that has been done then the obtained results : (1) the service quality is not good category (55.36%), (2) guest satisfaction are not satisfied category (44.64%), (3) hypothesis test result of simple linear regression obtained f countdown with sig. 0,000 < 0,05, then the service quality variables can explain the guest satisfaction significantly with the R Square of 0,372 that is where there is the influence of service quaity toward guest satisfaction of 33,5%. Keyword: service quality, guest satisfaction